Clear Cell Adenocarcinoma Arising from Endometriosis in the Groin: Wide Resection and Reconstruction with a Fascia Lata Tensor Muscle Skin Flap. (1st April 2018) - Yoshida, Shozo; Onogi, Akira; Kuwahara, Masamitsu; Uchiyama, Tomoko; Kobayashi, Hiroshi
Abstract : We herein report a case of clear cell carcinoma arising from endometriosis in the groin in a 53-year-old woman. The findings of MRI and FDG/PET-CT indicated a malignant tumor, and surgical biopsy confirmed adenocarcinoma of the female genital tract. The tumor including a part of the abdominal rectus muscle and rectus sheath, subcutaneous fat, skin, and the right inguinal ligament was resected en bloc . The defect in the abdominal wall was reconstructed with a fascia lata tensor muscle skin flap. The tumor was composed of clear cell adenocarcinoma arising from extrapelvic endometriosis. The patient received chemotherapy with gemcitabine and carboplatin for 6 cycles and had no evidence of recurrence 7 months after the treatment. We herein described the diagnosis and surgical management of endometriosis-associated carcinoma in the groin.